TRANSFORMASI â€œALFU LAILAH WA LAILAHâ€ - Farhah, Eva (Arabic Letters and Department, 2019)
This research tries to discover and reveal the transformation works from â€œAlfu Lailah wa Lailahâ€. The purpose of the discovery and disclosure of the works of transformation is to know the reader's attitude to the work